Relationship Between Big Five Personality and Pathological Internet Use: Mediating Effects of Loneliness and Depression - Zhou, Yong; Li, Hui; Han, Lei; Yin, Suyue (Frontiers in Psychology, 2021)
Pathological Internet use will have a serious impact on normal individual study and work and has become one of the most important factors hindering the growth and development of contemporary college students. The purpose of this study was to examine the mechanisms of loneliness and depression in the relationship between the Big Five personality traits and pathological Internet use (PIU). A total of 1179 college students were studied using the Chinese version of the Big Five Personality Scale, Loneliness Scale, Depression Scale, and Pathological Internet Use Scale. The results showed that loneliness partially mediated the relationship between extraversion and PIU and completely mediated the relationship between agreeableness and PIU and neuroticism and PIU. Depression completely mediated the relationship between agreeableness and PIU, neuroticism completely mediated the relationship with PIU, and sense of responsibility partially mediated the relationship with PIU. This study revealed the relationship between different personality traits and PIU and the mediating role of loneliness and depression, suggesting that we should carry out targeted interventions on PIU for college students with different personality traits.